Analisis Pendidikan Quran Surat Luqman Ayat 13-19 tentang Peran Ayah: Analysis of Quranic Education in Surah Luqman Verses 13-19: The Role of a Father - Rahmawati, Renti; Nurpriatna, Ade; Nurachadijat, Kun; Jaelani, Deny Ahmad (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
This study focuses on the essential role of fathers in children's education from the perspective of QS Luqman verses 13-19, serving as a foundation for Islamic character development amidst the decreasing involvement of fathers in modern families. The primary goal of this research is to understand and analyze how the values in these verses can guide fathers in shaping the moral and spiritual foundation of their children from an early age. Using a qualitative approach through literature review, data was gathered from prominent Quranic interpretations and relevant academic literature. Thematic analysis reveals that fathers play a critical role in character education by teaching values of monotheism, ethics, and practices of worship that reflect obedience to Allah SWT. Luqman’s example in QS Luqman 13-19 portrays a father instilling principles of patience, gratitude, and humility, advising his son on leading a life based on moral and spiritual integrity. This reinforces the view of fathers as not only providers but also primary educators in nurturing a spiritually and ethically resilient child. The study's implications highlight the importance of active father involvement in children’s moral upbringing, suggesting this as a basis for family policy and parenting approaches to mitigate adverse social influences. This research strengthens the perspective that the father's role in character education is vital for fostering individuals with strong moral character, integrity, and resilience.